2022
DOI: 10.5851/kosfa.2022.e8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Bovine Milk-Derived Extracellular Vesicles for Therapeutic Applications in Gut Health

Abstract: This manuscript does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In contrast to García-Martínez et al [ 582 ], who praise the generally “beneficial effects” of bovine MEX in metabolic interorgan cross-talk, we only see a meaningful potential use of MEX for infants of mothers who cannot provide adequate breastfeeding and depend on artificial formula administration. We must ask: What happens to the pancreatic β cells when bovine MEX are systemically administered over prolonged treatment periods with the intention to improve other chronic degenerative diseases such as osteoarthritis or osteoporosis [ 590 , 591 , 592 ], chronic inflammatory intestinal diseases [ 593 , 594 , 595 , 596 ], or chronic states of tissue fibrosis [ 597 , 598 ]?…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to García-Martínez et al [ 582 ], who praise the generally “beneficial effects” of bovine MEX in metabolic interorgan cross-talk, we only see a meaningful potential use of MEX for infants of mothers who cannot provide adequate breastfeeding and depend on artificial formula administration. We must ask: What happens to the pancreatic β cells when bovine MEX are systemically administered over prolonged treatment periods with the intention to improve other chronic degenerative diseases such as osteoarthritis or osteoporosis [ 590 , 591 , 592 ], chronic inflammatory intestinal diseases [ 593 , 594 , 595 , 596 ], or chronic states of tissue fibrosis [ 597 , 598 ]?…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous continuing studies are elucidating the functionality and role of livestock-derived EVs in livestock industry fields [44][45][46][47]. As the first to isolate rumen derived EVs, this study showed that REVs increased pathogen resistance by regulating nematode immune genes.…”
Section: Discussionmentioning
confidence: 89%
“…The use of concentrated MEX either native or uploaded with drugs will expose the recipient to increased amounts of intrinsic MEX miRs that may exert desired gene-regulatory effects in the target tissue but may adversely affect other non-target tissues. Bovine MEX showed beneficial effects in inflammatory bowel diseases and states of fibrosis (47)(48)(49)(50)(51)469), but may promote hyperphagia, obesity, T2DM, cancer and neurodegeneration (88,90,221,277,296,351) (Table 7). Certainly, human MEX are supportive for the newborn infant and contribute to the superiority of breastfeeding compared to formula.…”
Section: Discussionmentioning
confidence: 99%